War and peace in Africa's Great Lakes Region - Khadiagala, Gilbert M. (Palgrave Macmillan, 2020)
Contents: Security and governance in the Great Lakes region : an introduction Gilbert M. Khadiagala -- Burundi : between war and negative peace  Yolande Bouka -- The Democratic Republic of the Congo : an elusive peace  Jason K. Stearns -- Rwanda : setting the stage for 2017 and beyond Carina Tertsakian -- Uganda in the Great Lakes region : obstacles to peace and security Paul Omach -- The African Union's role in maintaining peace and security in the Great Lakes region  Solomon Dersso -- The European Union and the Great Lakes region : constraints and inconsistencies Marie V. Gibert -- The United Nations in the Great Lakes region  Emily Paddon Rhoads -- 9. Conclusions : reversing the spirals of conflict and instability in the Great Lakes region  Gilbert M. Khadiagala.